The arrogance of power : the secret world of Richard Nixon - Summers, Anthony; Swan, Robbyn (New York : Penguin Books, 2001)
Chronicles the life and political career of Richard Nixon, drawing from more than one thousand interviews and five years of research to provide an understanding of not only Nixon's dark political dealings but his peacemaking attempts and his troubled but long-lasting marriage.
Includes bibliographical references (pages 617-624) and index.
Keywords: Nixon, Richard M. (Richard Milhous), -- 1913-1994 -- Psychology; Presidents -- United States -- Biography